Investigating the therapeutic potential of a probiotic in a clinical population with chronic hand dermatitis - Gulliver WP; Hutton AS; Ship N (Dove Medical Press, 2018)
Wayne P Gulliver,1 Andrew S Hutton,1 Noam Ship2 1NewLab Life Sciences Inc., St. John’s, NL, Canada; 2Research and Development, Bio-K Plus International Inc., Laval, QC, Canada Background: Hand dermatitis or hand eczema (HD) is one of the most common dermatologic conditions. Lesions, scaling, pruritus and pain are chronic and relapsing. Improved HD has been reported with the probiotic composed of Lactobacillus acidophilus CL1285, Lactobacillus casei LBC80R and Lactobacillus rhamnosus CLR2 (Bio-K+). Purpose: Investigation of the therapeutic potential of this probiotic as the sole systemic treatment for adults with nonacute HD. Subjects and methods: A single-center study documented clinical ratings and patient-reported outcomes in adults with chronic HD. The probiotic was taken orally for 12 weeks, adjunctive to standard topical treatments and preventative measures. Results: Most of the 30 subjects with mild to severe HD were compliant with the probiotic. Around 22 of the 30 subjects were able to complete the study, and of these subjects, an improvement was noted in 19. One required systemic therapy, and one subject was not able to tolerate the probiotic and therefore discontinued the study. 23% of the subjects achieved clear or almost clear hands by the end of 12 weeks. Pruritus, which was a common complaint at baseline, was improved with 59% of symptomatic patients within 2 weeks. Conclusion: It is feasible and safe to administer Bio-K+ for HD. Clinicians saw an improvement in most subjects’ hands, and cases of significant improvement in dermatitis were documented. Pruritus was the most rapidly relieved symptom, as reported by patients. Keywords: hand dermatitis, eczema, CL1285, Lactobacillus, pruritus, Bio-K+